Enhancing Arabic Vocabulary Acquisition through Short-Form Video Content: TikTok and Instagram Reels as Learning Media - Viona Rosalina; Dinda Puspa Kirana; Syahrul Majid Simamora; Ummu Tsumairo; Aulya Rahmadhani Harahap (Universitas Pahlawan Tuanku Tambusai, 2026)
Short video content on social media platforms such as TikTok and Instagram Reels is increasingly being used as an informal learning medium, including in the context of Arabic language learning. This study aims to analyze the role of short video content, particularly on TikTok and Instagram Reels platforms, in improving Arabic vocabulary mastery through a literature review approach. This study employs a qualitative method by analyzing 10 scientific journal articles related to digital-based language learning, indexed between 2022 and 2026. The findings indicate that microlearning-based short video clips have great potential as a visual, interactive, and easily accessible learning medium. TikTok has proven relatively effective for initial introduction and brief vocabulary reinforcement, while Instagram Reels better supports the development of contextual and creative vocabulary use. The effectiveness of both platforms is influenced by the quality of content design, delivery strategies, and users' level of digital literacy. Nevertheless, challenges such as distraction and undirected use remain obstacles. Overall, the strategic use of short videos can serve as an effective alternative learning medium in the digital era, while also serving as an important consideration for teachers and curriculum designers in developing technology-based Arabic language learning.